Harmonizing platelet function analyzer testing and reporting in a large laboratory network. (26th June 2022) - Favaloro, Emmanuel J.; Mohammed, Soma; Vong, Ronny; Chapman, Kent; Kershaw, Geoffrey; Just, Sarah; Connelly, Lynne; Ryan, Michael; Zebeljan, Diane; Brighton, Timothy; Pasalic, Leonardo
Abstract: Introduction: The platelet function analyzer (PFA) is a popular platelet function screening instrument, highly sensitive to von Willebrand disease (VWD) and to aspirin therapy, with moderate sensitivity to defects in platelet function and/or deficiencies in platelet number. There are two models, the original PFA‐100 and the contemporary PFA‐200. Normal reference ranges (NRRs) provided by the manufacturer are the same for both models, instead being based on the type of test cartridge, for which there are two main ones: collagen/epinephrine (C/Epi) and collagen/adenosine diphosphate (C/ADP). Methods: Comparative evaluations of PFA testing and reporting in six different sites of a large pathology network, aiming to harmonize NRRs and test reporting across all network sites. A separate comparative study of testing a range of samples ( n > 150) on a PFA‐100 versus that on a PFA‐200. Review of contemporary literature. Results: Each site was identified to have a different reporting NRR, which after consolidating data permitted establishment of an agreed harmonized NRR for use across the network (C/Epi: 90–160; C/ADP: 70–124; based on n > 180). Similarly, each site reported and interpreted results in different ways, and after discussion and consolidation, a harmonized approach to interpretation and reporting was achieved. The separate comparative study of PFA‐100 versus PFA‐200 testing confirmed instrument equivalence. Conclusion: We achieved harmonized NRRs and reporting for PFA testing across a large pathology network. Our approach may be useful for other laboratory networks wishing to harmonize PFA testing.